THE INTERPLAY OF THE ANGIOTENSIN RECEPTOR BLOCKERS AND HAEMATOLOGICAL ABNORMALITIES: INSIGHTS AND IMPLICATIONS - Ghada Muthana Ahmed,; Alassaf, Fawaz Abdulghani; Abed, Mohammed Najim (Journal of Ayub Medical College Abbottabad, 2024)
Antihypertensive medications known as angiotensin receptor blockers (ARBs) have become increasingly popular for treating conditions beyond hypertension. The reason for this widespread use is mainly due to its reno-protective and cardioprotective properties in patients with congestive heart failure and diabetes mellitus. There have been conflicting studies on the relationship between ARBs and haematological abnormalities. Using the supplied search terms, we carried out a thorough search for relevant papers written in English and published before January 2024. All of the studies that met the selection criteria were searched for on PubMed, Cochrane Library, and Google Scholar. Based on the examined data from the searched literature, it has been demonstrated that angiotensin II is essential for the stimulation of erythropoiesis and inhibition of it by drugs such as ARBs can lower haematocrit levels, leading to anaemia. Accordingly, dose reduction or stopping the administration of ARBs could be a choice for the correction of anaemia. However, such a decision is based on the clinical situation and the requirements for other management options.